Research and Development on Galengdowo Village’s Tahu Walik Cracker Using Different Seasonings - Hadassah Elisha Karsten; Emre Omar Khaled; Oki Krisbianto; Magnalia Isnina Madyaratri; Fika Fatimah (Food Science and Technology Journal (Foodscitech), 2023)
Tahu walik is a snack product originating from Banyuwangi but has been developed in other areas such as Galengdowo Village, Jombang. To develop Galengdowo's tahu walik products that were able to compete inmarket, it was necessary to conduct research related to product sensory and consumer acceptance. The five sample variants used in this study were tahu walik without seasoning (T0), original seasoning (T1), balado seasoning (T2), salted pepper seasoning (T3), and commercial tahu walik (T4) for comparison. A total of 40 panelists conducted a hedonic analysis of the product's appearance in the packaging, shape, color, crispness, taste, and oily. The results showed that the highest purchase motivation was seen in T1 and T2, which were reddish, while the assessment of the packaging and sample's shape was not significantly different. The crispness value of T0 was the lowest compared to the other four samples which were not significantly different. Panelists most liked the taste of T3, T2, and T4 while T0 was the lowest, while the oily feeling was felt the most in sample T0 and the lowest in T2. Based on Simple Additive Weighting, T2 has the highest rank while T0 is the lowest. The difference in the type and color of the seasoning greatly influenced the panelists' preferences and their decision to buy tahu walik products. It can be concluded that the tahu walik processing industry in Galengdowo Village needs to develop its products to increase competitiveness in the market.